Odpowiedź:
1) a20 = (-1)×20×(2-20)
a20 = (-20)×(-18) = 360
a10 = (-1)×10×(2-10)
a10 = (-10)×(-8) = 80
a20 - a10 = 360 - 80 = 280
2) an = a1 + (n-1)×r
I
a5 = a1 + 4r
a6 = a1 + 5r
18 = a1 + 4r
21 = a1 + 5r
18-4r = a1
21 = 18-4r + 5r
21 = 18 + r
r = 3
18 = a1 + 4×3
a1 = 6
an = 6 + (n-1)×3
II
a1 + a7 = -8
a1 + a1 + 6r = -8
2×a1 + 6r = -8
a1 + 3r = -4
a1 = -3r - 4
a3 + a6 = -16
a1 + 2r + a1 + 5r = -16
2×a1 + 7r = -16
2×(-3r - 4) + 7r = -16
-6r - 8 + 7r = -16
r = -8
a1 = (-3)×(-8) - 4
a1 = 24 - 4 = 20
an = 20 + (n-1)×(-8)
3) x-3, 5, x+7
(x+7) - 5 = 5 - (x-3)
x + 2 = 8 - x
2x = 6
x = 3
0, 5, 10
r = 5